A Laminated Polymer Film Formulation for Enteric Delivery of Live Vaccine and Probiotic Bacteria. Issue 7 (6th May 2014) - de Barros, João M. S.; Scherer, Timothy; Charalampopoulos, Dimitrios; Khutoryanskiy, Vitaliy V.; Edwards, Alexander D.
<x xml:space="preserve">Abstract</x> Live bacterial cells (LBCs) are administered orally as attenuated vaccines to deliver biopharmaceutical agents and as probiotics to improve gastrointestinal (GI) health. However, LBCs present unique formulation challenges and must survive GI antimicrobial defenses including gastric acid after administration. We present a simple new formulation concept, termed polymer film laminate (PFL). LBCs are ambient dried onto cast acid‐resistant enteric polymer films that are then laminated together to produce a solid oral dosage form. LBC of a model live bacterial vaccine and a probiotic were dried directly onto a cast film of enteric polymer. The effectiveness at protecting dried cells in a simulated gastric fluid (SGF, pH 2.0) depended on the composition of enteric polymer film used, with a blend of ethylcellulose plus Eudragit L100 55 providing greater protection from acid than Eudragit alone. However, although PFL made from blended polymer films completely released low‐molecular‐weight dye into intestinal conditions (pH 7.0), they failed to release LBCs. In contrast, PFL made from Eudragit alone successfully protected dried probiotic or vaccine LBC from SGF for 2 h, and subsequently released all viable cells within 60 min of transfer into simulated intestinal fluid. Release kinetics could be controlled by modifying the lamination method. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2022–2032, 2014